HARGA, TESTIMONI DAN KUALITAS PRODUK: PENGARUHNYA TERHADAP KEPUTUSAN PEMBELIAN PRODUK BLACKDOFF PADA MARKETPLACE SHOPEE - Moh Yusuf Firmansyah; Ike Kusdyah Rachmawati; Mohammad Bukhori (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Price, testimonials and product quality influence the decision to purchase Blackdoff products on the Shopee marketplace. The purpose of this research is to determine and analyze 1) the influence of price on purchasing decisions, 2) the influence of testimonials on purchasing decisions, 3) the influence of product quality on purchasing decisions, 4) the influence of price, testimonials and product quality on purchasing decisions. The research location is in the city of Malang, the population in this study is consumers of Blackdoff products, with a sample of 100 respondents using a purposive sampling technique. The analysis technique uses multiple linear regression with SPSS for Windows 26.0 statistical analysis. The research results show that 1) price influences purchasing decisions, 2) testimonials influence purchasing decisions, 3) product quality influences purchasing decisions, 4) price, testimonials and product quality jointly influence purchasing decisions.